Investigation on Thrust Characteristics of a Downstream Offshore Floating Wind Turbine under Yawed Inflow Conditions - Yangwei Wang (MDPI AG, 2021)
In the natural marine environment, offshore floating wind turbines (OFWTs) inevitably experience yawed inflow conditions, which will make their aerodynamics more complicated than those experiencing uniform inflow conditions and difficult to understand. In the present study, the thrust characteristics of a wake-influenced OFWT under dynamic, static, and coupled yawed inflow conditions are investigated thoroughly. Analytical characterizations of yawed inflow and upstream wake are integrated into the blade element momentum (BEM) method to achieve the investigation. Based on this method, simulations by the FAST code have been conducted, and the results are analyzed. It is shown that the three inflow conditions have considerable influences on the thrust coefficient of the wind rotor or the normal force at the blade section, especially in the wake case where the downstream OFWT is located at a specific offset from the central line of a single upstream wake. In order to validate the analyses of simulation results, experimental tests by a set of dedicated apparatus are conducted. The comparison results are good, proving the reliability of simulation results. This work can provide some theoretical contributions to the aerodynamic design and control of OFWTs.